Crescimento e produção de plantios de paricá (Schizolobium amazonicum Huber ex. Ducke) sob diferentes espaçamentos - Santos, Elter Martins dos (2012)
This study aimed to analyze the effect of the spacing variable in the diameter growth of paricá; as well as to determine and project the diameter distributions of paricá at different ages; to evaluate the diameters movement at different ages, using the Percentual Entries method and to calculate the technical thinning ages and to provide estimates of production in quadratic diameter and volume per hectare, according to different spacings. It was used the Weibull probability density function for adjusting the diameter distribution models. Then, the future diameter distributions were projected using regression equations. After finding the diameter frequencies, the average percentual entries were obtained for each plot using a specific algorithm. From the percentual entries, a nonlinear regression model was adjusted, and through this model, the technical thinning ages were calculated for each spacing, based on the principles of the maximum curvature method. It was also tested the possible existence of interaction between spacing and ages, and then it was tested the effects of spacing on the growth of volume and quadratic diameter variables within each age by comparison of means by the Tukey test. A simple linear regression equation was fitted to examine the studied variables growth according to the floor area per plant. There was consistency and efficiency of the percentual entries method (PEM) in the study of the diameters movements. The technical thinning ages tends to be later in greater spacings, since the competition between the plants begins later. It was observed that there was an interaction (p <0.05) between the spacing and age factors on the paricá growth, showing a dependence between the factors. Despite the interaction, the higher quadratic diameter and lower mean volume in m³ha-1, was obtained in the 5 X 5 meters spacing, regardless of age. While the smallest spacing tested, 3 x 2 meters, had lower quadratic diameter and higher average volume, regardless of age